Systemic Therapy for Head and Neck Skin Cancers. (June 2021) - Knackstedt, Rebecca; Taub, Peter; Rogers, Gary; Gastman, Brian
The mainstay of curative therapy for head and neck skin cancers relies upon surgery and/or radiation therapy. However, for some aggressive, non-resectable or recurrent tumors, systemic therapy is necessary. Recent emerging classes of drugs have shown to improve survival for high-risk, recurrent, and unresectable variants of these tumors. The goal of this paper is to review options for systemic therapies for head and neck skin cancers including melanoma, non-melanoma skin cancers and other rare and non-malignant tumors.